Aortic microcalcification is associated with elastin fragmentation in Marfan syndrome. Issue 3 (21st September 2017) - Wanga, Shaynah; Hibender, Stijntje; Ridwan, Yanto; van Roomen, Cindy; Vos, Mariska; van der Made, Ingeborg; van Vliet, Nicole; Franken, Romy; van Riel, Luigi AMJG; Groenink, Maarten; Zwinderman, Aeilko H; Mulder, Barbara JM; et al.
Abstract: Marfan syndrome (MFS) is a connective tissue disorder in which aortic rupture is the major cause of death. MFS patients with an aortic diameter below the advised limit for prophylactic surgery (<5 cm) may unexpectedly experience an aortic dissection or rupture, despite yearly monitoring. Hence, there is a clear need for improved prognostic markers to predict such aortic events. We hypothesize that elastin fragments play a causal role in aortic calcification in MFS, and that microcalcification serves as a marker for aortic disease severity. To address this hypothesis, we analysed MFS patient and mouse aortas. MFS patient aortic tissue showed enhanced microcalcification in areas with extensive elastic lamina fragmentation in the media. A causal relationship between medial injury and microcalcification was revealed by studies in vascular smooth muscle cells (SMCs); elastin peptides were shown to increase the activity of the calcification marker alkaline phosphatase (ALP) and reduce the expression of the calcification inhibitor matrix GLA protein in human SMCs. In murine Fbn1 C1039G/+ MFS aortic SMCs, Alpl mRNA and activity were upregulated as compared with wild‐type SMCs. The elastin peptide‐induced ALP activity was prevented by incubation with lactose or a neuraminidase inhibitor, which inhibit the elastin receptor complex, and a mitogen‐activated protein kinase kinase‐1/2 inhibitor, indicating downstream involvement of extracellular signal‐regulated kinase‐1/2 (ERK1/2) phosphorylation. Histological analyses in MFS mice revealed macrocalcification in the aortic root, whereas the ascending aorta contained microcalcification, as identified with the near‐infrared fluorescent bisphosphonate probe OsteoSense‐800. Significantly, microcalcification correlated strongly with aortic diameter, distensibility, elastin breaks, and phosphorylated ERK1/2. In conclusion, microcalcification co‐localizes with aortic elastin degradation in MFS aortas of humans and mice, where elastin‐derived peptides induce a calcification process in SMCs via the elastin receptor complex and ERK1/2 activation. We propose microcalcification as a novel imaging marker to monitor local elastin degradation and thus predict aortic events in MFS patients. Copyright © 2017 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.